2014
DOI: 10.1021/nl404661u
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Description of the Role of Halides, Silver, and Surfactants on the Structure of Gold Nanorods

Abstract: Density functional theory simulations including dispersion provide an atomistic description of the role of different compounds in the synthesis of gold-nanorods. Anisotropy is caused by the formation of a complex between the surfactant, bromine, and silver that preferentially adsorbs on some facets of the seeds, blocking them from further growth. In turn, the nanorod structure is driven by the perferential adsorption of the surfactant, which induces the appearance of open {520} lateral facets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
184
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(203 citation statements)
references
References 49 publications
17
184
0
1
Order By: Relevance
“…Environments A and B favor {100} and high order {210} facets, respectively, which qualitatively mimics ab initio results of Almora-Barrios et al 43 for CTAB and CTASB adsorption on gold, respectively. Even though the strength, ϵ, of the gold− environment interaction is smaller in environment B, it is more strongly coordination dependent.…”
Section: Discussionsupporting
confidence: 83%
“…Environments A and B favor {100} and high order {210} facets, respectively, which qualitatively mimics ab initio results of Almora-Barrios et al 43 for CTAB and CTASB adsorption on gold, respectively. Even though the strength, ϵ, of the gold− environment interaction is smaller in environment B, it is more strongly coordination dependent.…”
Section: Discussionsupporting
confidence: 83%
“…bromide has been shown to be effective in transformation of Ag planar twinned morphologies into 3-D cubes and bipyramids by stabilizing (100) planes38. Bromide has been shown experimentally and computationally to strongly coordinate to silver and to drive selective facet stabilization in silver and gold nanoparticles40. In our work, the presence of bromide enables the transformation of 2-D bimorphic growth into 3-D by arresting platelet growth, first making them smaller and thicker (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…However, experimentally it has been found that objects such as nanorods can be systematically produced with an adequate selection of the solution growth. In that case the symmetry breaking appears very early in the formation of the seed as then some of the facets (but not all those equivalent by symmetry) can be blocked and in this way anisotropy can be easily induced [60]. A typical model for a metal surface in equilibrium with surfactants is shown in Fig.…”
Section: Reviewmentioning
confidence: 99%